1998
DOI: 10.1007/s000240050166
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of the Observed Wiechert Seismograph Magnification

Abstract: The paper presents results of experiments designed to measure the actual dynamic magnification of the Wiechert 1000 kg horizontal seismometer when excited by seismic waves. This is accomplished by comparing 51 digital records of seismic events recorded by the Wiechert and a well calibrated reference seismometer. The results obtained indicate that the magnification of the Wiechert seismometer is influenced by the interaction of its mass and frame, especially for high frequencies. This interaction has been model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on the result shown by Herak et al (1996Herak et al ( , 1998, we may attribute such overestimation to a possible underestimation of the dynamic magnification of mechanical instruments operating in Italy and surrounding countries up to about the beginning of the 1960's. Hence, we could also suggest that in future calibrations of macroseismic magnitude relationships, the data of earthquakes that occurred before 1960 (when well calibrated electromagnetic seismometers started to be installed in Italy and all over the World) be excluded.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on the result shown by Herak et al (1996Herak et al ( , 1998, we may attribute such overestimation to a possible underestimation of the dynamic magnification of mechanical instruments operating in Italy and surrounding countries up to about the beginning of the 1960's. Hence, we could also suggest that in future calibrations of macroseismic magnitude relationships, the data of earthquakes that occurred before 1960 (when well calibrated electromagnetic seismometers started to be installed in Italy and all over the World) be excluded.…”
Section: Discussionmentioning
confidence: 90%
“…The dynamic magnification of the Wiechert seismometer at different frequencies can be calculated using a theoretical formula, whose validity was questioned by Herak et al (1996Herak et al ( , 1998 on the basis of a comparison with a modern seismometer installed for reference at the same site in Zagreb (Croatia). They found that the real magnification of the Wiechert seismometer installed at such site, at frequencies of interest for Ms computations (0.05 Hz), could be significantly underestimated by the theoretical formula by a factor of 2, producing an overestimation of Ms up to 0.3 m.u.…”
Section: Homogeneity Of Magnitudes Reported By the Cpti15 Catalogmentioning
confidence: 99%
“…In order to carry out instrument response correction, the seismic traces have been corrected by specifying transfer function with the free period of pendulum (T o ), damping constant (h) and the magnification (V) of the instrument for mechanical sensors (Herak et al 1998). In fact, it is sometimes possible to find these values on the original seismograms even though it is a low possibility.…”
Section: The Instrument Response Correctionmentioning
confidence: 99%